IMPLEMENTATION OF THE PROGRAM KELUARGA HARAPAN (PKH) IN HEALTH UTILIZATION AND POSYANDU VISITS IN SIDO MAKMUR VILLAGE WEST MUNA REGENCY IN 2023 - Mutmainah, Mutmainah; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT The Family Hope Program, hereinafter referred to as PKH, is a program providing conditional social assistance to poor families who are designated as PKH beneficiary families (KPM-PKH). As a conditional social assistance program, PKH opens access for poor families, especially pregnant women, toddlers and the elderly, to utilize various health service facilities (faskes) available around them, including Posyandu in the village. Obligations of KPM PKH must be registered and present at health facilities and are obliged to attend and participate in Family Capacity Building Meetings (P2K2), namely educational activities (health education) for KPM PKH every month which aims to increase positive practices to encourage changes in maternal health behavior. Mothers who are beneficiaries of the PKH in terms of health and nutrition are intended to increase awareness of visiting posyandu every month. The research aims to analyze community behavior in utilizing health services and increasing posyandu visits for PKH participants in Sidomakmur Village. This research uses a descriptive qualitative approach with the Observation Method and the results were analyzed using content analysis. The research subjects were PKH participants. This research concludes that the behavior of the community in Sidomakmur village in utilizing health services by PKH participants in the form of posyandu visits has increased. Furthermore, it is recommended that every PKH KPM be given a Posyandu visit control card to maintain the commitment of PKH KPMs in their obligation to attend Posyandu every month. Keywords: PKH, Posyandu visits, P2K2